(untitled) (Revista Música, 1992)
Since its first presentation in the Eighteenth Century (ca. 1780) during the so-called "Civilização de Couro" period when the cattle raising was at its peak in Brazil, Bumba-meu-Boi continues to evolve, in spite of persecution by those in authority, by adapting to changes in social fabrics. This paper argues that Bumba-meu-Boi was created by the African slave in colonial Brazil. This assertion is sustained by several facts, primarily, the function for which the drama was created, to serve as a vehicle of social control used to denounce and to ridicule slave owners during colonial Brazil. Other styles which came into existence at later periods were created by other races of the population in imitation of the African by maintaining the story line of the play and its dramatization without necessarily adhering to the original raison d'être. Each of the new styles incorporated features which reflected its ethnic identity.